Institutions, ideas and regional policy (un-)coordination: The East African Community and the politics of second-hand clothing. Issue 2 (4th March 2023) - O'Reilly, Peter; Heron, Tony
Abstract: In this article, we engage with contemporary debates about South-South regionalism as spaces to advance collective development agendas. Our starting point is recent scholarship emphasizing regions as important political spaces where new development possibilities are being conceived in a changing global order. We build upon the emphasis this literature places on regions as sites of policy innovation but argue that insufficient attention has been paid to regional institutional dynamics. We explore these issues with reference to the East African Community (EAC) and its decision in March 2016 to 'phase-out' second-hand clothing imports, a decision which was soon abandoned by the majority of EAC states (the exception being Rwanda), following opposition from the US. While the EAC served as a crucial forum to conceive and promote this policy, we argue that its institutional foundations proved insufficient to produce the level of regional coordination necessary to ensure its implementation and to withstand external pressure. In this way, we also challenge the prevailing logic that portrays regional institutions in Africa as 'empty spaces' by both demonstrating the role of the EAC as a site of policy development and its institutional dynamics in shaping political outcomes.